Politik Hukum Ekonomi Syariah di Indonesia - Nevi Hasnita (Legitimasi: Jurnal Hukum Pidana dan Politik Hukum, 2012)
Legal policy is understood as the aims or policy direction taken by the government in making and implementing rules and regulations to achieve the state goal. The implementation of sharia economics in Indonesia, showed that the regulation is very fundamental to the growth and development of Islamic economics. In the first 10 years (1991-1999), the activities of Islamic economics were not well developed because it is not supported by adequate regulation. But in the second 10 years (2000-2011), there is a rapid progress in the area of Islamic banking, Islamic insurance, Islamic capital market, Syariah Obligation, Islamic mutual fund, microfinance institution, and Islamic public finance. This study concluded that the formal regulation and the economic policy of Indonesian government on the Islamic economics had been very positive. This means that the goverment has play a very good rules and support by setting a conducived formal regulation for supporting the sharia economics development in Indonesia.